P-208 A collaborative project to provide a rapid personalised care service (RPCS) for patients. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Moore, Judith; Tritton, Jackie; Richardson, Fay
Abstract : Background: February 2018, the CCG reported an overspend of the CHC (Continuing Health Care) budget, with delays in funding approval and sourcing care packages, resulting in patients dying without a care package or with inappropriate hospital admissions. Following the success of the West Hertfordshire Palliative Care Referral Centre (PCRC), (Hospice UK 2017 innovation in care award - a single point of access; three hospices and NHS community trust) three hospices collaboratively submitted a business case, proposing that any cost savings of 5% and above would be reimbursed to the hospices. July 2018 the CCG commissioned (18-month pilot) delivering NHS CHC fast track pathway. The RPCS launched Sept 2018. Aims of the RPCS: Provide personalised care by trained end of life care carers. Based with the PCRC, so supporting the wider triage and coordination of Palliative/end of life care across West Herts; Receive hospital and community fast track referrals for community care packages Service provision from 8–8, 24/7 plus dedicated budget for overnight care, (sub–contracted with Marie Curie); More patients achieving their preferred place of care/death; No acute hospital discharge delays whilst waiting fast track care; Reduction of inappropriate hospital admission; Improved patient experience in last weeks of life; Opportunity to reach more people by the hospices. Results to date (nine months): Deaths at home as a % of all deaths has risen; Preferred place of death risen from 79% to 90%; 99% of care delivered within 48 hours; Only 2% of patients have exceeded the CHC fast track criteria of 12 weeks; 100% of care has been sourced by the hospices; Rise in the initiation of care packages and referrals from the previous year's data; Ability to change care provision at short notice ensuring patient–centred and cost effective; 95% of referrals met CHC criteria, demonstrating effective budget control. Conclusions: Based on the current figures and activity the pilot is delivering care for an increased number of patients for less care hours than previously seen in CHC.